Quantifying Heat Losses In Micro Combustor With Wire Mesh Using Numerical Simulation - Abdul Munir, Fudhail; Mohd Ridzuan Tan, Nurfarah Diana; Mohd Tahir, Musthafah; Mikami, Masato (Penerbit Akademia Baru, 2020)
Micro power generation system is a field of study that has come into interest by many researchers due to the strong demands for low weight and long-life power sources of electronic devices. These has led to the increasement of meso and micro-scale combustion investigations. In order to fully understand more on this field of study, a numerical stimulation is utilized to investigate the effect of heat recirculation on the blowout limit for micro combustion. Four different combination of tube combustors is used to investigate their blowout limit such as quartz-brass tube combustion combination for unburned-burned region of micro combustor tube. The combination of tube combustors is then investigated using three-dimensional (3D) numerical simulation. The results suggested that by utilizing brass tube on either region of unburned or burned tube is able to improve the value of heat conducted on inner wall of via inner wall of the tube greatly. Due to the conductivity of brass tube is much larger than quartz tube, the improvement is expected